The Moral Status of an Entity in the Context of Bioethics - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
The issue of determining the moral status of an entity is a central topic in contemporary bioethical debates. It plays a particularly significant role in assessing the moral permissibility of practices such as euthanasia, abortion, the attribution of rights to animals, and various other bioethical concerns. This article examines four major approaches to defining moral status: speciesism, sentience, self-awareness and cognition, and finally, the gradual approach. As a result of the analysis, the application of the principle of speciesism is deemed morally unacceptable, while the principles based on sentience and on self-awareness/cognition, when considered independently, lead to theoretical ambiguities, internal contradictions, and fail to provide intuitively compelling justifications. Compared to the three key approaches mentioned above, the gradual approach has relative advantages. The gradual approach is the model of defining an entity’s moral status according to which moral status does not have a binary nature, but is expressed gradually. The gradual approach offers several comparative advantages: it is more flexible, intuitively persuasive, inclusive, and theoretically coherent.